Egg or eyeball? - Bell, Cece (Bell, Cece. Chick and Brain ;, 2020)
Oh! Oh, oh, oh! Look what Brain found. Chick and Spot say it is an egg. Brain says it is an eyeball. Is it an egg or an eyeball? The inimitable Cece Bell is back with a second hilarious primer on good manners gone awry and arguments run amok. Perfectly pitched to kids just learning to read and loaded with verbal and visual comedy, this offbeat graphic story by a master of the genre builds to an exhilaratingly absurd surprise ending.